Art experiments as stimulus for cultural creative processes: at the intersection of "positive" and "negative" psychology - Оніщенко, Олена (Київський національний університет імені Тараса Шевченка, 2024)
Background. The problem of the article is related to the beginning of the 20th century, when the concept of "artistic experiment" became a part of theoretical discourse. It was stimulated by a change of the art paradigm, caused by avant-garde. Such a transformation was based on the exhaustion of romanticism and naturalism and the powerful entry of the aesthetic and artistic principles of symbolism into the European cultural space. The gradual detachment of a part of artists from romanticism and naturalism led to the start of fundamentally new trends that formed the avant-garde movement. The article aims to apply a comparative analysis of "positive" and "negative" types of psychology to reveal the specifics of artistic experiments in the formation and development of the avant-garde movement. Methods. the article uses the potential of such methods as chronological (historicism), analytical (outlining of the components of the research process), historical retrospection (capability to operate with the concept of "negative" psychology), comparative (comparison of "positive – negative psychology"), typological (definition of psychological /mental state of the artist). Results. it is argued that the Franco-Italian-German artists who formed the core of avant-garde did not share the principles of classical arts, absolutizing both the freedom of creativity and its permissiveness. The article emphasizes that representatives of specific aesthetic and artistic trends of avant-garde – cubists, futurists, abstractionists, dadaists, surrealists – supported the spontaneity of the creative process. It was indicated that from the second half of the 19th century, the process of radical transformations can be traced both in the space of European humanities and in the literary and artistic fields. First, a kind of reorientation of the humanities takes place, it activates the interdisciplinary links and the situation of theoretical and practical parity. Second, cinematography emerges as a new kind of art that, relying on scientific and technical progress achievements, confidently "fits" into the cultural context. Third, at the turn of the 19th and 20th centuries, such new professions as film director, film producer, screenwriter, cameraman, sound engineer, etc. emerged and vastly affected a person's worldview by their work. Conclusions. In outlined conditions the role of psychology and psycho-physiology became significantly strengthened. It began to "cooperate" actively with other domains of humanities, in particular, aesthetics and art history.

Вступ . Проблематика статті пов'язана з початком ХХ ст., коли в теоретичний ужиток вводять поняття "художній експеримент", що стимулювався зміною мистецької парадигми, яка формується на засадах авангардизму. Така трансформація була спричинена вичерпаністю романтизму й натуралізму і потужним входженням у європейський культурний простір естетико-художніх засад символізму. Поступове відмежування від нього частини авангардистів зумовило появу принципово нових напрямів, що сформували авангардистський рух. Мета статті полягає в застосуванні порівняльного аналізу "позитивного" та "негативного" типів психології задля розкриття специфіки художніх експериментів у процесі становлення й розвитку авангардистського руху. Методи . у статті використано потенціал таких методів як хронологійний (засади історизму), аналітичний (окреслення складових частин дослідницького процесу), історичної ретроспекції (правочинність оперування поняттям "негативна" психологія), порівняльний (зіставлення "позитивна – негативна психологія"), типологійний (визначення психологічного/психічного стану митця). Результати . аргументовано, що франко-італійсько-німецькі митці, які формували ядро авангардизму, не поділяли засад класичного мистецтва, абсолютизуючи як свободу творчості, так і її вседозволеність. У статті наголошено, що представники конкретних естетико-художніх напрямків авангардизму – кубісти, футуристи, абстракціоністи, дадаїсти, сюрреалісти – підтримували спонтанність творчого процесу. Констатовано, що від другої половини ХІХ ст. простежується процес кардинальних змін і в просторі європейської гуманістики, і на літературномистецьких теренах. По-перше, іде своєрідна переорієнтація гуманітарних наук, що активізує міждисциплінарний зв'язок і ситуацію теоретико-практичного паритету; по-друге, виникає кінематограф – новий вид мистецтва, який, спираючись на здобутки науково-технічного прогресу, упевнено "вписується" в культурний контекст; по-третє – на межі ХІХ – ХХ ст. формується низка професій – кінорежисер, кінопродюсер, сценарист, оператор, звукорежисер та ін., доробок яких значною мірою впливає на світоставлення людини. Висновки . Можна висновувати, що в означених умовах значно підсилюється роль психології, психо-фізіології, які починають активно "співпрацювати" з іншими гуманітарними науками, зокрема естетикою та мистецтвознавством.
Художні експерименти як стимули культуротвірних процесів: на перехресті "позитивної" і "негативної" психології
Keywords: художній експеримент; "позитивна" і "негативна" психологія; культурологічний контекст; artistic experiment; "positive" and "negative" psychology; cultural studies context